Liturgical undoing: Christ, communion, and commodified bodies - Williams, Khalia J. (Review and expositor, 2018)
During the years of chattel slavery in the USA, Black bodies were commodified. This article pays particular attention to the commodification of female Black bodies and the way in which the participation of the Christian community in Holy Communion undoes the capitalistic, free market enterprise of commodification by setting bodies and communities of faith free from the abuse and bondage as we begin to live into the fullness of the body of Christ. At the table of Communion, we are undone and through the gracious gift of Christ's body we are reclaimed as the creation of the divine-a creation that God looks upon and calls good.